Schenker, Schubert, and the Subtonic Chord - David Damschroder (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
A close reading and critique of Heinrich Schenker’s treatment of the subtonic chord (for example, B♭-D-F in C major or C minor) serves as the foundation for a detailed assessment of the diverse contexts in which it was employed by Franz Schubert. Numerous analyses of musical excerpts by Schubert help to reveal the relationship between the subtonic chord and the dominant Stufe (scale-step) and to demonstrate various linear contexts in which it may arise. Although the chord often is labeled as VII in C minor or as ♭VII in C major, its subsidiary role within the projection or connection of more foundational Stufen warrants a less overtly harmonic interpretation. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part II).